Self-Determination theory and the darker side of athletic experience: The role of interpersonal control and need thwarting. - Bartholomew, K.; Ntoumanis, Nikos; Thøgersen-Ntoumani, Cecilie (2011)
Although research guided by self-determination theory has explored the conditions (i.e. autonomy support) and psychological processes (i.e. need satisfaction) that foster healthy development and effective functioning in athletes, very little research has considered the potential role of interpersonal control and psychological need thwarting in the development of athlete ill-being. To address these limitations, two new questionnaire measures were developed: the Controlling Coach Behaviours Scale and the Psychological Need Thwarting Scale. Analysis of subsequent data revealed that need satisfaction was predicted by autonomy-supportive behaviours whilst need thwarting was better predicted by coach control. In turn, athletes’ perceptions of need satisfaction predicted positive outcomes (i.e. vitality and positive affect) whereas need thwarting consistently better predicted maladaptive outcomes (i.e. disordered eating, burnout, depression, negative affect, physical symptoms, and perturbed physiological functioning). Such findings have important implications for the operationalisation and measurement of interpersonal styles and psychological needs both in sport and in other life domains.